Тhe Functional Education In The Process Of Literary Education (Journal of Pharmaceutical Negative Results, 2022)
The article describes the ways to apply the research method in the literary educational process. In particular, it discusses experimentsthat reflect an integrative approach to studying a learning topic, creative tasks, working on questions and answers, the fate of heroes,comparison of character traits, creating problem situations, and the relationship of a topic with real life.